Algorithmic Pragmatic Rationality: Street-Level Entrepreneurship in the Bazaar Economy on TikTok - Felaco, Cristiano; Luise, Vincenzo (Italian Sociological Review, 2026)
Second-generation social media platforms such as TikTok have become key infrastructures for the economic participation of street-level entrepreneurs operating within the bazaar economies of the Global South. In these contexts, characterized by heterogeneous economic forms shaped by pragmatism and adaptability, the ability to interpret and interact with TikTok’s algorithm is essential. Street-level entrepreneurs’ capacity to respond to algorithmic logic plays a crucial role in crafting engagement strategies aimed at sustaining their daily economic livelihoods. The ability of street-level entrepreneurs to interpret, respond to, and strategically interact with algorithmic logic is crucial to developing engagement practices aimed at sustaining daily economic livelihoods. This study conceptualizes these practices as forms of algorithmic pragmatic rationality – a situated, experiential mode of interaction with algorithmic systems oriented toward economic survival in marginal contexts. Adopting a user-centric perspective, this study employs semi-structured interviews with 16 street-level entrepreneurs who actively create content on TikTok to promote their businesses. It aims to investigate how they perceive and engage with the platform’s algorithmic system to attract consumers and increase revenue. The main findings reveal varying assumptions about TikTok’s algorithm, often reduced to a simplified notion of automated content visibility governing online virality. Participants also demonstrate a strong engagement in leveraging algorithmic logic for business advantage, while highlighting the emotional costs associated with the constant engagement required to maintain high levels of visibility. Forms of algorithmic awareness, strategic repertoires, and emotional impacts are creatively integrated into hybrid economic systems. In this sense, algorithmic engagement is not merely reactive. Still, it reflects a survival-oriented rationality that employs TikTok as a digital tool for active and situated economic participation in the context of the bazaar economy.